Pelatihan Pemahaman Konsep Geometri Berbasis Origami Bagi Siswa SD Negeri 1 Labuhan Ratu, Bandar Lampung - Notiragayu; Wamiliana; Asmiati; Widiarti (FT Universitas Lampung, 2025)
The Origami-Based Geometry Concept Understanding Training for Students of SDN 1 Labuhan Ratu, Bandar Lampung, aims to provide knowledge and an in-depth understanding of geometric building concepts to 20 students in grades 4 and 5 over 2 days as an effort to improve students' abilities and absorption of geometry materials in particular and mathematics more broadly. In this training, the lecture method is applied with slide presentation media, which is needed to explain the concept of geometric buildings and is varied with demonstrations of flat and spatial building models through origami paper demonstrations. Sample data were obtained from the results of the pre-test at the beginning of the training and the post-test at the end of the training. Then, from this paired data form, a hypothesis test was carried out to determine whether the two groups of data were significantly different or not. The results obtained showed an average increase of 22% after the training. This shows that students' absorption of origami-based geometry has improved.